Study on the probability of business loss due to low demand in the face of the COVID-19 health crisis in Latin America and the Caribbean - León, César (2021)
This research seeks to study the probability of business closure due to low demand during the COVID-19 health crisis in Latin America and the Caribbean to present conclusions and recommendations on economic recovery alternatives based on the results. It seeks to find which variables can significantly influence this closure, from an individual approach, focused on people who have their own or family business in the region. Studies that seek to explain the incidences in the probability of closure of a business with a focus on the individual as a business manager, are rare, particularly in the context of the pandemic. Traditionally, studies explain the closure of a business through its own variables. Contributions such as those of Sepúlveda and Reina (2016) or Bermúdez and Bravo (2019) show that variables such as indebtedness, reinvestment, leverage, among others, can be determinants of the closure of ventures.